Housing, population and region in Spain: a currently saturated property market with marked regional differences. - Serrano‐Martínez, José‐María; García‐Marín, Ramón; Lagar‐Timón, David (Geographical Journal, 2017)
In this paper we analyse the property market in Spain within a regional framework, according to the boundaries of the Spanish Autonomous Communities. Our analysis is based on the central hypothesis that there is an oversupply of housing in Spain, although there are some regional differences within this phenomenon. We first examine the stage known as the 'property boom', and we then produce an analysis that aims to simplify the housing market in Spain. After combining numerous variables and applying multivariate statistical techniques, we have obtained a classification with the following three categories: dried-up markets, saturated markets and less distressed markets. Our analyses confirm the fact that there are disparate realities throughout Spain, and even contrasting realities between the Autonomous Communities.